The normalisation and domestication of digital disinformation: on the alignment and consequences of far-right and Russian State (dis)information operations and campaigns in Europe. Issue 1 (2nd January 2021) - Innes, Martin; Innes, Helen; Roberts, Colin; Harmston, Darren; Grinnell, Daniel
ABSTRACT: This article traces a normalising and domesticating process in the use of digital misinformation and disinformation as part of political campaigning in Europe. Specifically, the analysis highlights innovations associated with the digital influence engineering techniques pioneered by far-right groups and agencies linked to the Kremlin, showing how there are areas of alignment and differentiation in the agendas and interests of these two groups. Their individual and collective activities in this area are important because of how they have promoted the use of similar disinforming tactics and techniques in the conduct of domestic politics.